Acute toxicity of non-ionized ammonia on tambacu (Colossoma macropomum x Piaractus mesopotamicus) (Revista Ciência Agronômica, 2020)
Ammonia is a toxic compound to aquatic organisms and at high concentrations in water, it can cause variouschanges in the animal. Therefore, it becomes important to determine the tolerance of farmed aquatic animals for that substance.Thus, the aim of this study was to determine the mean lethal concentration (LC50-96 h) of un-ionized ammonia (NH3) in tambacufingerlings (Colossoma macropomum x Piaractus mesopotamicus) in acute toxicity test. The fingerlings were exposed toammonia at concentrations of: 0.09 (control); 0.54; 1.23; 2.52; 3.44 and 3.66 mg L-1 NH3, which were obtained from theapplication of NH4Cl. The test lasted 96 hours and mortalities were recorded over that period. The LC50 was determined bythe Trimmed Spearman Karber statistical method. The LC50-96 h of non-ionized ammonia (NH3) for fingerlings of the tambacuhybrid was 1.63 mg L-1.